Delayed and Heterogeneous Effects of Flood Exposure on Hemorrhagic Fever with Renal Syndrome Risk: A Nationwide Spatiotemporal and Quasi-Experimental Study - Chuanlong Cheng; Hui Zuo; Yuqi Zhang; Jing Cai; Liang Lu; Xiujun Li (Environmental Health Perspectives, 2026)
Abstract Floods are increasingly frequent under climate change and may influence zoonotic disease transmission through environmental and ecological pathways. However, the spatiotemporal heterogeneity and potential causal relationship between floods and disease risk remain insufficiently characterized. We combined nationwide surveillance data on hemorrhagic fever with renal syndrome (HFRS) with multisource flood records in China from 2005 to 2022 to evaluate the association between flood exposure and HFRS risk. A Bayesian spatiotemporal hierarchical model was used to estimate lagged associations, identify high-risk clusters, and assess effect modification by environmental and socioeconomic factors. To strengthen causal inference, we further applied a stacked difference-in-differences design with propensity score matching. Flood exposure was associated with a biphasic lagged response in HFRS risk, characterized by a short-term decrease during the flood month and the subsequent month, followed by a delayed increase peaking at 4–6 months (maximum at 5 months: RR = 1.05, 95% CrI 1.02–1.08). Spatially, elevated risks were concentrated in flood-prone areas, particularly in northeast China. The delayed increase in risk was more pronounced in midtemperate regions, Apodemus-type endemic areas, and agricultural zones. Effect modification analyses indicated higher flood-associated risks in areas with lower socioeconomic status, including lower GDP, limited healthcare resources, and lower agricultural mechanization. The quasi-experimental analysis supported a causal association between flood exposure and increased HFRS risk, with the largest effect observed at approximately 3 months post-flood. These findings are consistent with environmentally mediated changes in host ecology and human exposure that may influence disease transmission following flood events. Our results provide evidence that flood exposure can increase zoonotic disease risk with a delayed and spatially heterogeneous pattern. Accounting for these lagged and context-specific effects may improve risk assessment and inform targeted public health interventions following extreme hydrological events.